Toward a limbic cortical inhibitory network: implications for hypothalamic-pituitary-adrenal responses following chronic stress - Radley, Jason J. (Frontiers in Behavioral Neuroscience, 2012)
A network of interconnected cell groups in the limbic forebrain regulates hypothalamic-pituitary-adrenal (HPA) axis activation during emotionally stressful experiences, and disruption of these systems is broadly implicated in stress-related psychiatric illnesses. A significant challenge has been to unravel the circuitry and mechanisms providing for regulation of HPA output, as these limbic forebrain regions do not provide any direct innervation of HPA effector cell groups in the paraventricular hypothalamus. Recent evidence will be highlighted that endorse a discrete region within the bed nucleus of the stria terminalis that acts as a neural hub for receiving and integrating these influences, whereas the prevailing view involves a layer of cell groups providing an array multisynaptic parallel pathways between the forebrain and PVH. A hypothesis will be advanced that accounts for the capacity of this network to constrain the magnitude and/or duration of HPA axis output in response to emotionally stressful experiences, and for how chronic stress-induced synaptic reorganization in key cell groups may lead to an attrition of these restraining influences in leading to HPA axis hyperactivity.